CHARACTERISTICS OF STYROFOAM WASTE-BASED MEMBRANE THROUGH VAPOR AND LIQUID-INDUCED PHASE INVERSION PROCESS - Silvana Dwi Nurherdiana; Bambang Wahyudi; Merry Jhoe Stefanny; Anita Karlina; Rachmad Ramadhan Yogaswara; Mohd Jumain Jalil; Hamzah Fansuri (Jurnal Kimia Riset, 2023)
Polymeric membrane-based-Styrofoam waste in the form of a thin sheet was successfully prepared by a phase-inversion technique in different final solidification treatments, namely, immersion and evaporation. This study aims to identify the effects of different solidification processes on membrane properties such as hydrophobicity, pore configuration, porosity, and membrane temperature stability. Characterization was carried out using contact angle, SEM, FTIR, TGA, and porosity tests. The results showed that an increase in Styrofoam 18-30 wt.% in dimethylformamide (DMF) as solvent decreases the hydrophobicity by 9.5%. The average contact angle of 62–80° indicated that the obtained membrane was prepared by immersion treatment. The membrane subjected to evaporation treatment was hydrophobic. Moreover, the microscopy image shows that the immersed membrane was denser than the evaporated membrane. This showed that a higher exchange rate between the solvent and non-solvent (water) produced a tight membrane than free evaporation in air. The polystyrene membrane from Styrofoam exhibited excellent temperature stability up to 350 °C. In addition, the mechanical strength was affected by employing different solidification processes. The obtained results were also successfully tabulated from a statistical point of view to validate the conclusions. The following information can provide basic knowledge for modifying membrane-based-Styrofoam to optimize zero-waste goals.